Pensamientos irracionales por desempleo en un adulto de 47 años de edad del barrio El Troje de la ciudad de Riobamba - Morales Toro, Daniel Arnulfo (2020)
This case study research prior to obtaining the third-level academic title, Clinical Psychologist mention. In line with the fulfillment of the objective, I refer to the fact that it focuses on evaluating various criteria that support the psychic principles of the mental structure of a 47-year-old patient, pseudonym Jhony, same as going through a painful accident as a result finds himself unemployed for several years for different reasons related to his way of visionary interpreting his existence. Unemployment is a reality that affects many people in terms of search applicants must meet the standards of the job. The fact of being rejected several times is frustrating, so that a number of irrational beliefs and thoughts are generated. Through the cognitive behavioral therapeutic approach and integrating the principles of rational emotional behavioral therapy, we identify those irrational thoughts and beliefs that generate sadness, despair and discomfort. Once identified, they proceeded through cognitive restructuring, metaphors and other effective techniques to gradually modify them. In an understandable way, we proceeded to explain to Jhony how thoughts generate emotions and how the human being becomes an evaluation machine through the VAKOG system, sight, hearing, kinesthetic, olfactory, taste. The psychotherapeutic intervention was multiple in relation to the patient, being satisfactory.